PENERAPAN METODE SUZUKI DALAM PEMBELAJARAN BIOLA DENGAN PENDEKATAN BERBASIS WARNA PADA ANAK AUTISM SPECTRUM DISORDER (ASD) DI SLB NEGERI SUKOHARJO - Sarah Suryandari Hasanatussabili; Siti Aesijah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning violin for students with Autism Spectrum Disorder (ASD) presents particular challenges, especially in understanding abstract musical concepts such as notation, pitch, and finger positioning. Conventional teaching methods are often less effective for students who rely more on visual and concrete stimuli. This study explores the implementation of the Suzuki method combined with a color-based approach in violin learning at SLB Negeri Sukoharjo. Using a qualitative case study design, data were collected through observation, interviews, and documentation. The findings indicate that the learning process is carried out in a structured manner through listening, imitation, and repetition, supported by color coding to simplify musical understanding. The use of colors helps students recognize notes and finger positions more easily, leading to improved focus, engagement, and learning motivation. Psychologically, students tend to be more cooperative and responsive during the lesson, although challenges such as fluctuating mood and limited attention span remain. Evaluation is conducted through performance-based assessment with flexible criteria adapted to students’ abilities. Overall, this approach not only facilitates musical learning but also supports cognitive and emotional development, making it a relevant alternative for inclusive music education.